(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
George Bernard Shaw (1856-1950), an Irish playwright, critic, and Nobel Prize winner of 1925, was one of the most celebrated authors of his age. His works are known to be influenced by Ibsenism and naturalism. He revolutionised the use of comedy in theatre by combining sharp social critique with humour. Arms and the Man (1894), one of his most well-known plays, represents an early and commercially successful instance of Shaw’s “pleasant plays.” His plays are divided into two categories– the initial ones as ‘Plays Unpleasant’ and the later ones as ‘Plays Pleasant.’ The play Arms and the Man is subtitled as, “An Anti-Romantic Comedy,” which perfectly signals Shaw’s intention to overthrow the romantic notions of war and heroism that dominated the literary and theatrical landscape of his time. This paper analyses how Shaw employs various rhetorical devices such as paradox and parody to critique nationalism, romantic idealism, and class hierarchy, making Arms and the Man an anti-war comedy that remains relevant even today.